2022
DOI: 10.3390/diagnostics12092153
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Exosomes and Exosomal RNAs Isolated from Post-Mortem Body Fluids for Molecular Forensic Diagnosis

Abstract: Exosomes have been mainly studied for their potential applications in biomarker detection and drug delivery for diagnosis and treatment. However, in the field of forensic research, the potential value of exosomes derived from post-mortem body fluids has not been investigated to date. Here, we isolated the exosomes and exosomal RNAs from post-mortem body fluids, including cardiac blood, pericardial fluid, and urine. We also compared commercial exosome isolation kits to determine the optimal method for post-mort… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…4 Previous studies have shown that it is feasible to isolate EVs from post-mortem body fluids, and EVs RNAs are well-preserved, which could be used for forensic diagnosis. 52 It has been considered that miRNAs in EVs play an important role in cardiovascular diseases and may be able to provide objective evidence of SCD identification in forensic diagnosis. 53 In our study, we found that miR-208b-3p and miR-143-3p in EVs derived from plasma were significantly upregulated in ACS patients experiencing SCD compared with HC.…”
Section: Discussionmentioning
confidence: 99%
“…4 Previous studies have shown that it is feasible to isolate EVs from post-mortem body fluids, and EVs RNAs are well-preserved, which could be used for forensic diagnosis. 52 It has been considered that miRNAs in EVs play an important role in cardiovascular diseases and may be able to provide objective evidence of SCD identification in forensic diagnosis. 53 In our study, we found that miR-208b-3p and miR-143-3p in EVs derived from plasma were significantly upregulated in ACS patients experiencing SCD compared with HC.…”
Section: Discussionmentioning
confidence: 99%